Combination of BMI1 and MAPK/ERK inhibitors is effective in medulloblastoma. Issue 8 (25th February 2022) - Badodi, Sara; Pomella, Nicola; Lim, Yau Mun; Brandner, Sebastian; Morrison, Gillian; Pollard, Steven M; Zhang, Xinyu; Zabet, Nicolae Radu; Marino, Silvia
Abstract: Background: Epigenetic changes play a key role in the pathogenesis of medulloblastoma (MB), the most common malignant pediatric brain tumor. Methods: We explore the therapeutic potential of BMI1 and MAPK/ERK inhibition in BMI1 High ;CHD7 Low MB cells and in a preclinical xenograft model. Results: We identify a synergistic vulnerability of BMI1 High ;CHD7 Low MB cells to a combination treatment with BMI1 and MAPK/ERK inhibitors. Mechanistically, CHD7-dependent binding of BMI1 to MAPK-regulated genes underpins the CHD7-BMI1-MAPK regulatory axis responsible of the antitumour effect of the inhibitors in vitro and in a preclinical mouse model. Increased ERK1 and ERK2 phosphorylation activity is found in BMI1 High ;CHD7 Low G4 MB patients, raising the possibility that they could be amenable to a similar therapy. Conclusions: The molecular dissection of the CHD7-BMI1-MAPK regulatory axis in BMI1 High ;CHD7 Low MB identifies this signature as a proxy to predict MAPK functional activation, which can be effectively drugged in preclinical models, and paves the way for further exploration of combined BMI1 and MAPK targeting in G4 MB patients.